Inactivating BTK mutations in large B‐cell lymphoma in a real‐world cohort: Strong correlation with BCL2 translocation. Issue 3 (24th June 2022) - Schejbel, Lone; Breinholt, Marie Fredslund; Gang, Anne Ortved; Nielsen, Torsten Holm; Pedersen, Lars Møller; Høgdall, Estrid; Nørgaard, Peter
Abstract: Inactivating mutations in Bruton's tyrosine kinase ( BTK ) in patients with follicular lymphoma (FL) have recently been reported. These mutations were found in BTK inhibitor‐treatment naïve patients. Here, we report the BTK mutation status in a real‐world cohort of patients with non‐Hodgkin lymphoma. We found primary BTK mutations in 7.7% of patients with large B‐cell lymphoma (LBCL) and in 14.1% of patients with FL. All patients with BTK ‐mutated LBCL were BCL2 translocation positive, and the correlation between BCL2 translocation and BTK mutation persisted even when patients with known transformation from FL were excluded.